Empacotamento de agregados reciclados para concretos vibrocompactados - Hermann, Aline (2016)
Recycled aggregates have been widely studied and used in some areas of civil engineering. Among its most common applications can include: revetment mortar, bases, sub-bases, and subgrade pavements, precast concrete elements, containment works and landfills. The main factor that hinders the use of recycled aggregate in concrete is related to the mortar layer adhered to the surface. This layer has high porosity and therefore high water absorption, which gives the concrete, lower workability, and increased content of superplasticizers and water, which in turn increases the consumption of cement in order to ensure the compressive strength. These factors increase the cost of the concrete. The particles packing, among other things, studying the proper particle size distribution and particle morphology, as well as the incorporation of additives and mineral additions such that the voids content is minimized and optimum workability to concrete with particular application. Proper adjustment of these parameters allows an increase mechanical strength of the concrete with the same cement content or, maintains the strength with reduction in the cement content. Thus, the objective of this work is to apply particles packing techniques in recycled concrete aggregates in order to evaluate the effectiveness of this tool in the dry concrete compositions used in paving blocks with compression mechanical strength to greater than 35 MPa. For this, the recycled concrete aggregates produced by different equipment of 4 different companies located within a radius of 100 km from the city of Curitiba - PR, were characterized for: morphology, particle size distribution, density, bulk density, void ratio, mass and visual composition and water absorption. Then, it was chosen the aggregate more favorable physical characteristics to the best packing, on the basis of morphology and the particle size analysis and the values of: water absorption, density and bulk density. Chosen the aggregate particles was applied to two packing packing models: Funk and Dinger (Alfred) of 1980 and De Larrard of 1999, with and without the introduction of cement in particle size distribution. With the ideal proportions of aggregates were then studied by means of consistometer "VeBe", the amount of water for each concrete mix. The compositions that showed the best results were tested for water absorption, mechanical resistance to axial compression, tensile strength by diametrical compression and microstructural analysis by Scanning Electron Microscope. The concrete was cast by the same laboratory vibro-compression machine used by Lima (2009), which consists of a vibrating table and steel rollers applied on the molds, to simulate the compaction force of industrial vibro-compression machine. Within the standard deviation considered the packing packing model of Funk and Dinger with the introduction of cement particle size analysis showed the best results with respect to compression strength at 28 days and for the absorption of water. A lab equivalent time of vibro-compression to industrial machines can be found and this time becomes greater when using recycled aggregates. Moreover, with the same consumption of cement concrete with recycled aggregates achieved mechanical strength within the standard deviation of concretes produced with natural aggregates used by precast industries.